Structural and functional insight of New Delhi Metallo β-lactamase-1 variants. (January 2018) - Khan, Sidra; Ali, Abid; Khan, Asad U
New Delhi Metallo β-lactamase-1 (NDM-1) is a member of the Metallo-β-lactamase family, capable of catalyzing the hydrolysis of all β-lactam antibiotics. The rapid dissemination of NDM producers, 'superbugs', has become a worldwide concern to health workers. Seventeen different variants of NDM have been reported so far, across the world. These variants varied in their sequences either by single or multiple amino acid substitutions. This review summarizes the crystal structure of NDM and provides a comparative analysis of all variants. Moreover, we have for the first time highlighted the role of α-helix, β-sheet and loop structures of NDM enzyme, having different mutations occurred in these regions. The effect of these substitutions on its structure and functional aspect has to be thoroughly understood to design effective inhibitors in future.